2017
DOI: 10.1088/1741-4326/aa6938
|View full text |Cite
|
Sign up to set email alerts
|

Material properties and their influence on the behaviour of tungsten as plasma facing material

Abstract: The views and opinions expressed herein do not necessarily reflect those of the ITER Organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…As a result, the precipitate of W has attracted great interest of many researchers. [ 5–16 ] Recently, Wirtz et al [ 5 ] experimentally investigated the effect of material properties, and W behavior showed that different production processes had certain effects on the anisotropic microstructure and the related material properties of W in the initial state while improving the recrystallization behavior, but thermal shock performance had little impact. Mannheim et al [ 6 ] used a multiscale model to study the long‐term microstructure evolution of W under cascade damage conditions and the distribution of W in nuclear fusion reactor steering gear at different irradiation temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the precipitate of W has attracted great interest of many researchers. [ 5–16 ] Recently, Wirtz et al [ 5 ] experimentally investigated the effect of material properties, and W behavior showed that different production processes had certain effects on the anisotropic microstructure and the related material properties of W in the initial state while improving the recrystallization behavior, but thermal shock performance had little impact. Mannheim et al [ 6 ] used a multiscale model to study the long‐term microstructure evolution of W under cascade damage conditions and the distribution of W in nuclear fusion reactor steering gear at different irradiation temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Pure tungsten (W) is considered for plasma-facing materials of the fusion reactors including diverter components [1][2][3][4]. For fusion applications, tungsten has various advantages such as high melting point, high thermal conductivity, low tritium retention, and low material erosion for application as diverter materials [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, the testing temperature may have been too low in that analysis to improve the ductility (below the brittle-to-ductile transition temperature, which is reported to increase by recrystallization). On the other hand, there are also examples in literature where the ductility of tungsten increases after recrystallization, such as by Wirtz et al [7], who found for several grades of tungsten a significantly improved uniform elongation and total elongation in post-recrystallization (accompanied by a lower yield strength), or [8], where fracture strains were reported of 17% and 22% prior to recrystallization and 68% after recrystallization. The impurity content of the tungsten grade may play a role in the grain boundary cohesion [9], which can affect the ductility.…”
Section: Introductionmentioning
confidence: 99%